Biofortified Wheat Increases Dietary Zinc Intake: A Randomised Controlled Efficacy Study of Zincol-2016 in Rural Pakistan - Lowe, Nicola M.; Zaman, Mukhtiar; Khan, Muhammad Jaffar; Brazier, Anna K. M.; Shahzad, Babar; Ullah, Ubaid; Khobana, Gul; Ohly, Heather; Broadley, Martin R.; Zia, Munir H.; McArdle, Harry J.; Joy, Edward J. M.; et al. (Frontiers in Nutrition, 2022)
A new variety of zinc biofortified wheat (Zincol-2016) was released in Pakistan in 2016. The primary aim of this study was to examine the effects of consuming Zincol-2016 wheat flour on biochemical and functional markers of zinc status in a population with widespread zinc deficiency. An individually-randomised, double-blind, placebo-controlled cross over design was used. Fifty households were recruited to participate in the study, with each household included at least one woman of reproductive age (16-49 years) who was neither pregnant nor breast feeding or currently taking nutritional supplements. All households were provided with control flour for an initial 2-week baseline period, followed by the intervention period where households were randomly allocated in a 1:1 ratio to receive biofortified flour (group A; n=25) and control flour (group B; n=25) for 8-weeks, then switched to the alternate flour for 8-weeks. The trial has been registered with the ISRCTN (https://www.isrctn.com), ID ISRCTN83678069. The primary outcome measure was plasma zinc concentration, and the secondary outcome measures were plasma selenium and copper concentrations, plasma copper:zinc ratio and fatty acid desaturase and elongase activity indices Nutrient intake was assessed using 24-hour dietary recall interviews. Mineral concentrations in plasma were measured using inductively coupled plasma mass spectrometry and free fatty acids and sphingolipids by mass spectrometry. Linear Mixed Model regression and General Linear Model with repeated measures were used to analyse the outcomes. Based on an average flour consumption of 224 g/day, Zincol-2016 flour provided an additional daily zinc intake of between 3.0 mg and 6.0 mg for white and wholegrain flour respectively. No serious adverse events were reported. This resulted in significant, increase in plasma zinc concentration after 4 weeks (mean difference 41.5 µg/L, 95% CI (6.9 to 76.1), p=0.02). This was not present after 8 weeks (p=0.6). There were no consistent significant effects of the intervention on fatty acid desaturase and elongase activity indices. Regular consumption of Zincol-2016 flour increased the daily zinc intake of women of reproductive age by 30-60%, however this was not associated with a sustained improvement in indices of zinc status.